FREQUENCY OF DIABETIC KETOACIDOSIS IN DIABETIC PATIENTS - Ghulam Abbas Sheikh; Dilshad Muhammad (Journal of University Medical & Dental College)
ABSTRACT Objective To determine the frequency of diabetic ketoacidosis in diabetic patients. Study design Cross sectional study Place and duration of study Department of medicine DHQ Hospital and Aziz Fatimah Hospital, Faisalabad from July 2010 to December 2010. Materials and methods One hundred and forty diabetic patients of either sex and age more than 15 years with fasting plasma glucose level 126 mg/dL or higher on more than one occasion were included in study. Random plasma glucose, arterial blood gases and urine ketones were done to diagnose diabetic ketoacidosis.Patients with stroke, and hepatic and uremic encephalopathy were excluded. Quantitative variables like age, plasma glucose levels, blood ph and serum bicarbonate were recorded as mean and standard deviation. Qualitative variables like sex and urine ketones were recorded as frequency and percentage. Results The mean age of the patients was 50.8±14.3 years. There were 54(38.6%) male and 86(61.4%) female patients. Mean fasting plasma sugar was 211±60.9 mg/dL and 208±50.6 mg/dL on two different occasions. Mean random plasma glucose was 337.1±79 mg/dL.There were 20 (14.3%) patients whose urine for ketones was positive, and their blood pH was <7.3 and serum bicarbonate was <15 mEq/L.So diabetic ketoacidosis was found in 20 (14.3%) patients and 120 (85.7%) patients did not have diabetic ketoacidosis. Conclusion It is concluded from this study that diabetic ketoacidosis is common in patients with diabetes mellitus occurring in 14.3% of all cases.